The connections of Locus Coeruleus with hypothalamus: potential involvement in Alzheimer’s disease - Giorgi, Filippo Sean (J Neural Transm (Vienna), 2021)
The hypothalamus and Locus Coeruleus (LC) share a variety of functions, as both of them take part in the regulation of the sleep/wake cycle and in the modulation of autonomic and homeostatic activities. Such a functional interplay takes place due to the dense and complex anatomical connections linking the two brain structures. In Alzheimer’s disease (AD), the occurrence of endocrine, autonomic and sleep disturbances have been associated with the disruption of the hypothalamic network; at the same time, in this disease, the occurrence of LC degeneration is receiving growing attention for the potential roles it may have both from a pathophysiological and pathogenetic point of view. In this review, we summarize the current knowledge on the anatomical and functional connections between the LC and hypothalamus, to better understand whether the impairment of the former may be responsible for the pathological involvement of the latter, and whether the disruption of their interplay may concur to the pathophysiology of AD. Although only a few papers specifically explored this topic, intriguingly, some pre-clinical and post-mortem human studies showed that aberrant protein spreading and neuroinflammation may cause hypothalamus degeneration and that these pathological features may be linked to LC impairment. Moreover, experimental studies in rodents showed that LC plays a relevant role in modulating the hypothalamic sleep/wake cycle regulation or neuroendocrine and systemic hormones; in line with this, the degeneration of LC itself may partly explain the occurrence of hypothalamic-related symptoms in AD.